Cleavage of the precursor coat protein of black beetle virus strain w17 in rabbit reticulocyte lysate - Blackhurst, Diane Mary (Rhodes University, Faculty of Science, Department of Biochemistry, Microbiology and Biotechnology, 1988)
Black beetle virus (BBV) is a bipartite single-stranded RNA virus belonging to the family Nodaviridae. Its host range has been found to be limited to insects. RNA 1, the larger of the two RNA molecules, with a MW of 1,15 x 10â ¶ and the smaller RNA 2 with a MW of 0,46 x 10â ¶, are both packaged in the same virus particle. The two RNA molecules are translated separately, with RNA 1 coding for protein A of MW 105 x 10Â³ and RNA 2 coding for protein Î± of MW 47 x 10Â³. Protein Î± is the major capsid protein precursor, which during in vivo maturation is cleaved to form the coat protein Î² of MW 43 x 10Â³, and protein Î³ of MW 5 x 10Â³. Cell-free translation of BBV (strain W17) mRNA was carried out in rabbit reticulocyte lysates. Protein Î± was detectable between 0 and 30 minutes after RNA addition. A protein 'Î²', which was found to co-electrophorese on polyacrylamide gels with authentic Î² and which was immunoprecipitated by anti-BBV antiserum, was detectable after 30 minutes. Results of this work show that the formation of 'Î²' could be prevented by the addition of RNase to the lysate, indicating that intact RNA is necessary for Î± to Î² cleavage. Arresting protein synthesis by the addition of cycloheximide to the lysate mix did not inhibit the cleavage. The formation of Î² could also be prevented by cooling the lysate mix to 1Â°C. Cleavage of Î± to Î² still occurred when RNA 2, without the presence of RNA 1, was translated. Therefore the cleavage is not dependent on a translation product of RNA 1. Sedimentation of lysate on sucrose density gradients showed that Î± to Î² cleavage was not accompanied by assembly of BBV RNA and protein lnto a viral substructure as has been shown to occur with some viruses, for example certain picornaviruses. Serial dilution of lysate containing Î± showed that the level of Î² decreased with increasing dilution, indicating that the cleavage is not mediated by autocatalysis, but by some other unknown factor. Although much work has been carried out on black beetle virus, no work has been published to date concerning Î± to Î² cleavage as an indication of assembly in rabbit reticulocyte lysates. Results of these cell-free translation experiments thus indicate that BBV coat protein precursor Î±, in association with its messenger RNA 2, undergoes a maturation cleavage in the lysate to produce BBV coat protein Î². In addition, this cleavage seems to occur without assembly into any intermediate viral structure
Keywords: Beetles; Insects -- Viruses